EXPLORATORY STUDY OF NEAR AND SUPERCRITICAL CARBONDIOXIDE WARM PASTEURIZATION ON NILE TILAPIA - Sugeng Pondang Sugiharto; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Yudi Pranoto (AGROINTEK, 2020)
Effects of both near critical and supercritical CO2 pasteurization on inactivation of muscle protease and lipase of red tilapia (Oreochromis niloticus) were investigated along with its impact on microbial reduction and physical appearance. Near critical phase was designed at 70 bar and supercritical phases were designed at 80 and 90 bar.  It was found that CO2 pressure had greater effect on protease inactivation  than on lipase inactivation. Temperature increase did not improve both protease and lipase inactivation while fillet texture was adversely affected. The fillet color experienced color changes significantly.